Expropriation Law: Velasco resurrected (Thanks Humala!). Registry Qualification died (Thanks to whom?) - Ortiz Pasco, Jorge (2015)
This article analyzes two central points, which are the expropriation from a criticism on what the new Expropiation Law indicates; and from that law, the author will refer about the role of registration qualification and how it has developed in practice. Finally, the author concludes three important issues that they have been derived from the analysis of the law, and presents the conclusions through a critique to the issue of property in our country.